The processing at low temperatures of Tl2Ba2Ca1Cu2Ox films in argon atmospheres for microwave devices - OConnor, J; Bramley, A; Morley, S; Jenkins, A; Doole, R; Grovenor, C; Goringe, M; DewHughes, D (1995)
Epitaxial Tl-2212 films have been grown on LaAlO3, MgO and ceria-buffered R-plane sapphire using an ex-situ anneal step in argon atmospheres at temperatures of 720-740 degrees C. Films grown on LaAlO3 have T-c's of 101 - 105.5K, large-area J(c)'s of up to 2x10(5) Acm(-2) and surface resistances (R(3)) as low as 3.7m Ohm (80K, 10GHz). TEM and HREM show the films to be well-aligned and relatively fault-free. Films grown on ceria-buffered R-plane sapphire have T-c's up to 100.5K and large-area J(c)'s up to 1x10(5) Acm(-2).